Healthcare policies, precautionary measures and outcomes of mass gathering events in the era of COVID-19 pandemic: Expedited review - Ahmed A. Alahmari; Anas A. Khan; Fahad A. Alamri; Yasir S. Almuzaini; Alia K. Habash; Hani Jokhdar (Elsevier, 2024)
With the onset of the COVID-19 pandemic in early 2020, several countries suspended or restricted mass gathering (MG) events to mitigate the risk of superspreading events. Prohibiting MGs aimed to lessen the likelihood of highly infectious persons coming into close contact with many others. Now that the world has opened its doors wide and removed most of precautionary measures, many questions arise. In this review, we aimed to summarize the current evidence regarding the policies and regulations that were implemented for the safe return of MG events. Besides, we highlighted the impact of the return of MG events during 2021 on the trajectory of COVID-19 spread. Canceling MG events can carry religious, societal, economic, and public negative consequences necessitating the safe return of these events. The experience with the COVID-19 pandemic was the foundation for the recommendations for the safe conduction of MG events during the pandemic by international public health bodies. When policymakers adequately applied precautionary measures and strategic approaches, we witnessed the safe holding of huge MG events without aggravating the COVID-19 situation or increasing the number of new cases beyond the capacity and readiness of the national healthcare system.